(3cTa GdhGajI aj TQM GdcGajIs - (3GdMdHj, eMeO Hf YeQ SQGL GdOjf, J (B850(3g`s
(3ChdgG (B:s
(3dc GdMeO jG ef UQa bdhHfG fMh GdeYGfj hGdHjGf hQUa aj fahSfG HOGFY GdYdhe hGdJHjGfs
(3BNQgG (B:s
(3hdfNJe GdcJGH HgPg GdBjI GdTQjaI hfMeO Gddg ChdG hBNQG Ydi eG TQafG HGdhUhd Edi GdEJeGe hJaVd YdjfG HJjSjQ GdGNJRGe Efg hdj GdEfYGe hGdehUd Edi GdeQGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 315s
(3eYLe GdeDdajf(B: 3 / 560s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs